The biodiesel market and public policy: A comparative analysis of Argentina and Brazil - Flexor, Georges Gérard (2012)
This article presents a comparative case study of the institutional aspects of policymaking and the impacts that this has had on the development of the biodiesel market in Argentina and Brazil. The study draws upon an analysis of the policymaking process and, based on the available statistical evidence, discusses how this has influenced the market’s development. Its findings underscore the differences between the two countries’ policy objectives. In Argentina, issues relating to the supply of petrodiesel have been a crucial factor, whereas, in Brazil, the promotion of family farming has been a major objective. In Brazil, Petrobras has played a significant role, but some of the country’s policy objectives in this area have not been fully met. In Argentina, the external market continues to be the driving force behind this industry.